(untitled) (Semiárida, 2020)
Seven species, wild and cultivated, of Lathyrus (L. crssslpes Gillies ex Hooker et Amott, L. /stifolius Linné, L. macropus Gillies ex Hooker et Amott, L. maguellanicus Lamarck var maguellanicus, L. odoratus Linné, L. pubescens Hooker et Amott, L. tomentosus Lamarck), from Southem Córdoba Province, Argentina, are described and iIIustrated. Key of identification, distribution and uses are provided.